Control through Compassion: Legitimizations of Surveillance, Dynamics of Power, and the Role of the Expert in the Finnish Makeover TV Shows Jutta and the Super Diet and Jutta and the Half-Year Super Diet. Issue 4 (2nd October 2021) - Ritter, Susanne
ABSTRACT: Disciplinary practices on the gendered fat body are a central aspect of weight-loss makeover TV shows; however, they are subtle and hard to identify. I ask how surveillance and control are legitimized as appropriate methods for achieving bodily change in the Finnish makeover shows Jutta ja Superdieetit (Jutta and the Super Diet) and Jutta ja Puolen Vuoden Superdieetit (Jutta and the Half-Year Super Diet) and how the experts reinforce unequal power structures. The ethos of equality is very strong in Finland, which is also apparent in the special construction of the expert as "one of the team". The research material is examined in light of Michel Foucault's theories of power and the concept of docile bodies, and as part of postfeminist media culture in which the ideas of "freedom of choice" and "submission as empowerment" are crucial. The choices for the participants of the makeover shows are, however, very limited, leaving just enough freedom so that they accept the power dynamics they are entangled in. I argue that control and surveillance are legitimized as means of helping participants achieve their ideal body and life. Instead of breaking existing power dynamics, the construction of the expert as attentive and caring works to reinforce these structures since discipline is enacted in the "best interest" of the participant. The dynamics of (disciplinary) power are thus subtle and work in a particularly hidden way.